2006
DOI: 10.1128/iai.00970-06
|View full text |Cite
|
Sign up to set email alerts
|

Globally Distributed Mycobacterial Fish Pathogens Produce a Novel Plasmid-Encoded Toxic Macrolide, Mycolactone F

Abstract: Mycobacterium ulcerans and Mycobacterium marinum are closely related pathogens which share an aquatic environment. The pathogenesis of these organisms in humans is limited by their inability to grow above 35°C. M. marinum causes systemic disease in fish but produces localized skin infections in humans. M. ulcerans causes Buruli ulcer, a severe human skin lesion. At the molecular level, M. ulcerans is distinguished from M. marinum by the presence of a virulence plasmid which encodes a macrolide toxin, mycolacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
126
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 32 publications
6
126
0
Order By: Relevance
“…Based on some phenotypic traits that distinguished it from M. ulcerans, such as photochromogenicity, absence of growth at 37°C, and scant growth at 30°C on Middlebrook 7H10 agar, this mycobacterium was given a new species designation, Mycobacterium pseudoshottsii. Subsequent analysis of the strain showed that it too contained a pMUM-like plasmid with the mycolactone mls genes and that it made yet another mycolactone, called mycolactone F (26). In the same study, a cluster of M. marinum strains that had been isolated from diseased fish in the Red and Mediterranean Seas (38) were also positive for mls gene sequences, and they too produced mycolactone F (26).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Based on some phenotypic traits that distinguished it from M. ulcerans, such as photochromogenicity, absence of growth at 37°C, and scant growth at 30°C on Middlebrook 7H10 agar, this mycobacterium was given a new species designation, Mycobacterium pseudoshottsii. Subsequent analysis of the strain showed that it too contained a pMUM-like plasmid with the mycolactone mls genes and that it made yet another mycolactone, called mycolactone F (26). In the same study, a cluster of M. marinum strains that had been isolated from diseased fish in the Red and Mediterranean Seas (38) were also positive for mls gene sequences, and they too produced mycolactone F (26).…”
mentioning
confidence: 82%
“…Subsequent analysis of the strain showed that it too contained a pMUM-like plasmid with the mycolactone mls genes and that it made yet another mycolactone, called mycolactone F (26). In the same study, a cluster of M. marinum strains that had been isolated from diseased fish in the Red and Mediterranean Seas (38) were also positive for mls gene sequences, and they too produced mycolactone F (26). One of these strains (DL240490) shared identical hsp65 gene sequences with M. pseudoshottsii and another fish pathogen, Mycobacterium seriolae (28).…”
mentioning
confidence: 99%
“…For this reason, the deprotection was quenched at approximately 60% completion, and the recovered triol was recycled. After one recycle, synthetic mycolactones A and B were isolated in 67% yield as an approximately 3:2 mixture of 4′-Z (mycolactone A) and 4′-On comparison of 1 H NMR (Figure 2), 13 C NMR (Table 1), and TLC [silica gel, CHCl 3 -MeOH-H 2 O (90:10:1)], the synthetic mycolactones A and B were found to be superimposable on the natural mycolactones A and B, respectively. Rigorously speaking, however, these comparisons could not eliminate the possibility that the synthetic mycolactones A and B might be the remote diastereomers 25 of the natural products.…”
Section: 14mentioning
confidence: 99%
“…Flash chromatography (100:1 hexanes/EtOAc) gave the vinyl iodide 25 (1.413 g, 65% yield). 1 , 9H), 0.056 (s, 3H), 0.054 (s, 3H), 0.04 (two overlapped singlets, 6H); 13 Synthesis outlined in Scheme 10-To a solution of t-BuOK (6.56 g, 58.5 mmol) in THF (400 mL) at -78 °C was added Z-2-butene (8.2 g, 146 mmol) followed by n-BuLi in hexanes (2.16 M, 27.1 mL, 58.5 mmol). The bright yellow suspension was stirred at -78 °C for 5 min, -45 °C for 10 min, and then -78 °C for 15 min.…”
Section: Synthesis Outlined In Schemementioning
confidence: 99%
See 1 more Smart Citation